Constructive Solutions of Foundations and Foundations of Buildings: Solusi Konstruktif untuk Pondasi dan Fondasi Bangunan - Abdurashidovna, Egamberdiyeva Shakhnoza (Indonesian Journal of Innovation Studies, 2024)
This study systematically examines various types of building foundations to elucidate their structural characteristics and performance. Through a comprehensive review and categorization, we identify key typologies including shallow foundations, deep foundations, and specialized variants such as mat foundations and pile foundations. Employing a combination of literature review and empirical analysis, we elucidate the distinct advantages and limitations of each foundation type in terms of load-bearing capacity, stability, and resilience against environmental factors. Results underscore the importance of selecting foundation types tailored to specific soil conditions, structural requirements, and geographical contexts, highlighting implications for enhancing building resilience, minimizing construction costs, and promoting sustainable urban development. Highlights: Various types of building foundations are systematically examined to elucidate their structural characteristics and performance. The study identifies key typologies including shallow foundations, deep foundations, and specialized variants such as mat and pile foundations. Results underscore the importance of selecting foundation types tailored to specific soil conditions, structural requirements, and geographical contexts for promoting sustainable urban development. Keywords: Building Foundation, Foundations, Types Foundation, Soil, Foundation Quality.